Severe fibrosis of the pancreas in chronic pancreatitis: main pathological components, immunophenotype of fibrogenic cells and collagen - V. О. Tumanskiy; I. S. Kovalenko (Patologìâ)
Pathomorphological feature of chronic pancreatitis (CP) is the development of pancreatic fibrosis with the accumulation of various collagen types, tubulin, fibronectin, laminin, and also intermediate filament proteins produced by activated pancreatic stellate cells (PSCs), which express the cytoskeletal α-smooth muscle actin (α-SMA).